Integration of waste heat recovery systems of thermal power plants into urban infrastructure: case study of hot water supply f or the “Usolsky” district of Pavlodar using heat pumps (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study analyzes the feasibility of utilizing the low-grade heat of cooling water from the Aksu Thermal Power Plant (TPP) to provide domestic hot water (DHW) for the “Usolsky” district of Pavlodar. The paper presents the results of thermodynamic and techno-economic analyses of a heat pump system of the water-to-water type (Mammoth MCRH-0140), which uses the waste heat of the Irtysh River. It is shown that the use of heat pumps with a coefficient of performance (COP) ≈3.6 significantly reduces the specific fuel consumption for thermal energy generation and decreases carbon dioxide emissions by more than 2,500 tons per year. The main design parameters of the projected heat pump station (HPS), calculated energy consumption, economic performance, and payback period (approximately 5.9 years) are presented. The implementation of the proposed scheme demonstrates a high potential for integrating low-grade heat sources into urban thermal infrastructure and can serve as a pilot model for the transition to fourth- and fifth-generation district heating systems (4GDH/5GDHC) in Kazakhstan.
Keywords: waste heat, heat pump, TPP, DHW, energy efficiency